Socio-Economic Status of Workers in Fisheries Processing Facilities: The Sample of the Black Sea - Mehmet Emin Erdem; Şennan Yücel; Selahattin Çoban (Turkish Journal of Agriculture: Food Science and Technology)
It is aimed to determine the socio-economic status of the people working in the seafood processing facilities in the Black Sea Region. A questionnaire was applied to a total of 102 sector employees working in 7 seafood processing plants operating in the Region to determine their social and economic status. There were 24 questions in the questionnaire and it was attempted to determine the socio-economic data of the participants such as age, gender, education level, working time, residence ownership, monthly income, and leisure time. The average working hours of the employees in their facilities are 1-5 years, the monthly income of 40.2% is between 2001-2500 TL. It has been determined that the personnel participating in the survey are 90.2% workers, 2% foremen, 2% technicians and 3.8% engineers.